Benefits of a Hearing Registry: Cochlear Implant Candidacy in Quiet Versus Noise in 1,611 Patients - Dunn, Camille; Miller, Sharon E.; Schafer, Erin C.; Silva, Christopher; Gifford, René H.; Grisel, Jedidiah J. (American journal of audiology, 2020)
Purpose This retrospective study used a cochlear implant registry to determine how performing speech recognition candidacy testing in quiet versus noise influenced patient selection, speech recognition, and self-report outcomes. Method Database queries identified 1,611 cochlear implant recipients who were divided into three implant candidacy qualifying groups based on preoperative speech perception scores (≤ 40% correct) on the AzBio sentence test: quiet qualifying group, +10 dB SNR qualifying group, and +5 dB SNR qualifying group. These groups were evaluated for demographic and preoperative hearing characteristics. Repeated-measures analysis of variance was used to compare pre- and postoperative performance on the AzBio in quiet and noise with qualifying group as a between-subjects factor. For a subset of recipients, pre- to postoperative changes on the Speech, Spatial and Qualities of Hearing Scale were also evaluated. Results Of the 1,611 patients identified as cochlear implant candidates, 63% of recipients qualified in quiet, 10% qualified in a +10 dB SNR, and 27% qualified in a +5 dB SNR. Postoperative speech perception scores in quiet and noise significantly improved for all qualifying groups. Across qualifying groups, the greatest speech perception improvements were observed when tested in the same qualifying listening condition. For a subset of patients, the total Speech, Spatial and Qualities of Hearing Scale ratings improved significantly as well. Conclusion Patients who qualified for cochlear implantation in quiet or background noise test conditions showed significant improvement in speech perception and quality of life scores, especially when the qualifying noise condition was used to track performance.